PENGARUH FASILITAS PAJAK DAN LEVERAGE TERHADAP MANAJEMEN PAJAK (Studi Kasus Pada Perusahaan Sub-Sektor Kimia Yang Terdaftar di BEI pada Tahun 2017-2019) - Rizky Daniel Rivaldi Tambunan; Harman Malau (Jurnal Ekonomis, 2021)
This study aims to show whether the effect of tax facilities and leverage on tax management in the chemical sub-sector in the years listed on the Indonesian stock exchange in 2017-2019. This research was conducted using quantitative methods, the research method to be carried out was purposive sampling method and the researchers collected various kinds of companies, namely 30 companies. The data used is secondary data on the financial statements of every chemical sub-sector company listed on the Indonesia Stock Exchange in 2017-2019. The method of testing this sample by researchers is used with the results of the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, r test, f test, t test. The way the researcher analyzes this data is by using multiple linear regression. The results of this study inform and conclude that tax facilities have an effect on tax management while leverage has no effect on tax management.